Jung, Winnicott and the divided psyche. Issue 3 (18th May 2016) - Saban, Mark
Abstract: In his review of Memories Dreams Reflections, Winnicott diagnosed Jung as suffering from a psychic split, and characterized the content and the structure of analytical psychology as primarily moulded and conditioned by Jung's own defensive quest for a 'self that he could call his own'. This pathologizing analysis continues to be endorsed by contemporary Jungian writers. In this paper I attempt to show that Winnicott's critique is fundamentally misguided because it derives from a psychoanalytic model of the psyche, a model that regards all dissociation as necessarily pathological. I argue that Jung's understanding of the psyche differs radically from this model, and further, that it conforms by and large to the kind of dissociative model that we find in the writings of Frederic Myers, William James and Theodor Flournoy. I conclude that a fruitful relationship between psychoanalysis and analytical psychology must depend upon an awareness of these important differences between the two psychic models.